(untitled) (Collection of scientific works «Modern structures of metal and wood», 2024)
Minerals processing produces two main products: a commercial product (concentrate, pellets) and tailings (waste from ore processing). The tailings are stored in a tailings storage facility (TSF), a special hydraulic structure for receiving and storing solid and liquid mineral processing waste. The focus is primarily on ensuring the reliability and safety of these facilities during their design, construction, and operation, as a failure of such structures can have catastrophic consequences. This paper computes the statistics of tailings dam failures using an up-to-date database on failures. The retrospective review covers the period from 1915 to 2024. During this time, about 373 cases of tailings dam failures were recorded. The historical trend regarding the number of failures has an average of 3.42 failures per year. The majority of failures occurred between 1960 and 2000 (230 failures), accounting for approximately 62% of the total number of accidents. In the 2000s, a decrease in the number of incidents compared to previous decades was observed, while after 2010, there is a tendency for an increase in the number of incidents (5.9 failures per year). The accidents in tailings dam breakages occur mostly in North America (41%). Statistical data analysis shows that the main causes of failures are overtopping (21%), slope instability (16%) and seismic instability (15%). The analyses of the distribution of the world’s tailings dam failures with regard to dam height show that 90% of the cases occurred in dams less than 50m in height and only 2% of incidents in dams higher than 100 m. The correlations between stored and released volumes have been verified using a database. Based on the relationship found from the regression analysis, as the tailings volume increases by 1%, the release volume increases by 0.25%. Statistical data analysis of tailings dam failures allowed for the identification of the most vulnerable and least reliable elements of the structures of TSF, which will allow them to be used in the probability analysis of accidents at these structures.